IMPACT OF ADDUCTOR STRENGTHENING ON SPRINT TIME AND AGILITY IN FOOTBALL PLAYERS (International Journal of Physiotherapy, 2020)
Background: The ability to tackle and dribble the ball swiftly past the rival player forms an important ball based football skill. Agility plays a crucial role for the players to gain good control over the ball. A combination of good agility with good sprint time is undoubtedly a distinguishing characteristic of elite level players. Football as a sport requires a rapid change of directions and speed several times during a match. This particular action requires the player to apply force rapidly into the ground, thereby putting a lot of stress on the adductor muscles. This research paper focuses on the impact of hip adductor exercises and their influence on agility and sprint time in football players.Methods: This interventional study was carried out on 131 male elite level football players playing from clubs and football academies in and around Mumbai city. All the players were assessed for 30 M sprint test, T-Test, and Dribble time test to assess sprint and agility pre and post-intervention. An adductor strengthening intervention consisting of 8exercises were performed for over four weeks.Results: Paired T-test was used to analyze the data, which showed statically significant improvement with p-value 0.000 (